Polymorphisms in the cytotoxic T lymphocyte-associated protein-4 immune regulatory gene and their impact on inhibitor development in patients with hemophilia A - Aveen M. Raouf Abdulqader; Ali Ibrahim Mohammed; Shwan Rachid (Journal of International Medical Research, 2019)
Objective The development of inhibitors against infused factor VIII represents the most severe complication of substitution therapy in hemophilia A (HA) patients. Data on risk factors for inhibitor formation in Iraqi Kurdish patients with HA are unavailable. This study aimed to evaluate the impact of two single nucleotide polymorphisms (SNPs) in an immune regulatory gene in the emergence of inhibitors. Methods We focused on 126 patients with either severe or mild/moderate HA presenting with and without inhibitors. We analyzed the frequency of two polymorphisms in the cytotoxic T lymphocyte-associated protein-4 gene ( CTLA-4 ; CTLA-4-318C > T and CTLA-4 + 49A > G). Genotyping was performed using restriction fragment length polymorphism–PCR and direct sequencing. Results We found no significant correlation between the CTLA-4-318 C > T T allele and inhibitor development among patients with severe or mild/moderate HA. However, a significantly high inhibitor risk was detected for the CTLA-4 + 49 A > G G allele (odds ratio [OR] = 3.1, 95% confidence interval [CI] = 1.383–7.024) and (OR = 4, 95% CI = 1.719–9.437) among patients with severe and mild/moderate HA, respectively. Conclusion We conclude that the CTLA-4 +49 A > G SNP plays a substantial role as a potential risk determinant for inhibitor formation in Iraqi Kurdish patients with HA.